Machine learning and data mining in pattern recognition 7th International Conference, MLDM 2011, New York, NY, USA, August 30 - September 3, 2011. Proceedings - Perner, Petra (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 7th International Conference on Machine Learning and Data Mining in Pattern Recognition, MLDM 2011, held in New York, NY, USA. The 44 revised full papers presented were carefully reviewed and selected from 170 submissions. The papers are organized in topical sections on classification and decision theory, theory of learning, clustering, appilication in medicine, Webmining and information mining; and machine learning and image mining.